ENT300 Choco More / Afifah Zainal... [et al.] - Zainal, Afifah; Lapis, Olivia Magritta; Abdul Manan Ibrahim, Ridzwan; Alexander Entebang, Stephanie; Ahmad, Wan Aszmeelrolzaman (2011)
This business is based on partnership where it consists of five (5) members. The members consist of the General manager, Administration Manager, Marketing Manager, Operational Manager and Financial Manager. There are criteria and conditions that have to be fulfilled which require the involvement of effort and precision of producing our goods. Without such conditions, the business cannot run properly and organizational goals will not be achieved. These conditions must be achieved in order for the business to take position in the first place. The stated conditions need to be prepared beforehand before starting the business. All the major aspects of planning have to be considered in order to ensure proper management of the business in obtaining the goals of the organization.